2009
DOI: 10.1063/1.3132785
|View full text |Cite
|
Sign up to set email alerts
|

The competition between the liquid-liquid dewetting and the liquid-solid dewetting

Abstract: We investigate the dewetting behavior of the bilayer of air/PS/PMMA/silanized Si wafer and find the two competing dewetting pathways in the dewetting process. The upper layer dewets on the lower layer (dewetting pathway 1, the liquid-liquid dewetting) and the two layers rupture on the solid substrate (dewetting pathway 2, the liquid-solid dewetting). To the two competing dewetting pathways, the process of forming holes and the process of hole growth, influence their competing relation. In the process of formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…Dewetting 1-50 and electric field induced instabilities of thin liquid layers [89][90][91][92][93] and bilayers [48][49][50][81][82][83][84][85][86][87][94][95][96] have emerged as promising techniques for mesoscale pattern formation. Large-area ordered polymer patterns find diverse applications in the fabrication of micro-and optoelectronic devices, biosensors, microfluidic devices and fuel and solar cell technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Dewetting 1-50 and electric field induced instabilities of thin liquid layers [89][90][91][92][93] and bilayers [48][49][50][81][82][83][84][85][86][87][94][95][96] have emerged as promising techniques for mesoscale pattern formation. Large-area ordered polymer patterns find diverse applications in the fabrication of micro-and optoelectronic devices, biosensors, microfluidic devices and fuel and solar cell technologies.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting here that the values obtained even for positive induction times are noisier than for the bilayer system (for example, for the 270 nm PS film within 2.5 mm V825T layers, t 0 ¼ 12 ± 130 s). Finally, it should be noted that for 400 nm PMMA layers, in both the bilayer and trilayer case, dewetting of the PMMA on the glass slide could also occur, as has been studied by Xu et al [38] However, with the polymers chosen and the experimental conditions of this study, it is always much slower than the dewetting of the PS film.…”
Section: Trilayer Systemmentioning
confidence: 65%
“…The difference of solubility and resultant dewetting speed leads to the formation of Bbottom SAN droplets covered by the upper PMMA islands.^Moreover, slow dewetting, which can be attributed to the poor solubility of PMMA in DMF, and consequent forced movement (driven by the dewetting and the structure evolution of bottom SAN layer) account for the random distribution of holes. Both theoretical and experimental investigations indicated that the viscosity, surface energy, and film thickness produce noticeable effect on the stability and structure evolution in the bilayer films [16,[31][32][33]. Particularly, in the upper-PS/bottom-PMMA system, G. Krausch and his co-workers showed that the viscosity of PS and PMMA, controlled by means of molecule weight, plays an important role in the dewetting of them [34].…”
Section: Resultsmentioning
confidence: 97%